2016
DOI: 10.1097/md.0000000000002875
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of the Effects of Xingnaojing Injection on Consciousness Disturbance

Abstract: Xingnaojing (XNJ) is commonly extracted from Angongniuhuang, a classic Chinese emergency prescription, and widely used in the treatment of nervous system disorders including consciousness disturbance in China.To evaluate the beneficial and adverse effects of XNJ injection, on consciousness disturbance.Seven major electronic databases were searched to retrieve randomized controlled trials designed to evaluate the clinical efficacy of XNJ alone or combined with Western medicine in treating consciousness disturba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 5 publications
(5 reference statements)
0
12
0
Order By: Relevance
“…AGNH is widely used in acute cerebrovascular conditions including stroke, encephalitis and meningitis for hundreds of years ( Guo et al, 2014 ; Wu et al, 2016 ; Fu et al, 2017 ). However, due to the well-known hepatorenal toxicity of cinnabar and realgar in AGNH, it has been controversial for the usage of AGNH in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…AGNH is widely used in acute cerebrovascular conditions including stroke, encephalitis and meningitis for hundreds of years ( Guo et al, 2014 ; Wu et al, 2016 ; Fu et al, 2017 ). However, due to the well-known hepatorenal toxicity of cinnabar and realgar in AGNH, it has been controversial for the usage of AGNH in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The commercialized injectable product of Xingnaojing Injection was extracted and refined scientifically from classic Chinese emergency prescription "Angong Niuhuang Pill", it had the functions of clearing heat and detoxication, cooling blood and activating blood circulation, inducing resuscitation and widely used in the treatment of intracerebral haemorrhage, cerebral ischemia, and nervous system disorders in China [78][79][80]. In view of critical cases with COVID-19 might suffer from consciousness disturbance, Xingnaojing Injection had major biological effects to relax the cerebral vascular and protect the mature neuron, in vivo and in vitro research, it was confirmed that the mechanism of cerebrovascular protection might be relevant to the activation of PI3K/ Akt/eNOS signaling pathways and the suppression of NLRP3 inflammasomes [81,82].…”
Section: Therapeutic Potentials For Severe or Critical Patientsmentioning
confidence: 99%
“…Quality control results confirm the reliability of clinical XNJ preparations. Both clinical trials and basic experiments have shown that XNJ can improve brain injury, promote consciousness recovery, and provide neuroprotective effects in stroke (Xu et al 2014;Wu L et al 2016;Ma et al 2017;Zhang et al 2018). However, the specific effects and mechanisms of XNJ on the cerebral I/R remains unclear, which limits further clinical application.…”
Section: Introductionmentioning
confidence: 99%